2004
DOI: 10.1097/00007691-200402000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of a New Cyclosporine A Formulation to Neoral®

Abstract: New cyclosporine A (CsA) formulations must prove their bioequivalence to Neoral, the reference CsA formulation, to allow free prescription for the patients. The aim of this study was to compare the pharmacokinetics (PK) of a new CsA formulation (Zinograf-ME), produced by Strides-Arcolab, to Neoral and to demonstrate their interchangeability in stable renal transplant recipients. Twelve-hour PK studies were obtained from 18 (13 M/5 F) adult patients (mean age 44.7 +/- 12 years). They received their renal allogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Study designs included randomized controlled trials (n=17; eight crossover and nine parallel), non-randomized interventional studies (n=15), and observational studies (n=18; cohort and before/after designs). Innovator drugs studied included Neoral (cyclosporine; n=32 studies,31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 28 in kidney transplants, three in heart transplants, and one in liver transplants), Prograf (tacrolimus; n=12 studies,63 64 65 66 67 68 69 70 71 72 73 74 seven in kidney transplants, one in heart transplants, one in liver transplants, and three in a mixture of liver, kidney, or heart transplants), and Cellcept (mycophenolate mofetil; n=6 studies,75 76 77 78 79 80 five in kidney transplants and one in liver transplants). Neoral was compared with 12 different generics (Iminoral, Equoral, Gengraf, Cysporin, Zinograf-ME, Neoplanta, Consupren, SangCya (Sang-35), Sigmasporin Microral, Pliva, Cicloral, and Arpimune); Prograf was compared with four different generics (Tacni, Tacrobell, Adoport, and Sandoz-tacrolimus); and Cellcept was compared with five different generics (Myfenax, Medis, Linfonex, Mycept, and Myconol).…”
Section: Resultsmentioning
confidence: 99%
“…Study designs included randomized controlled trials (n=17; eight crossover and nine parallel), non-randomized interventional studies (n=15), and observational studies (n=18; cohort and before/after designs). Innovator drugs studied included Neoral (cyclosporine; n=32 studies,31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 28 in kidney transplants, three in heart transplants, and one in liver transplants), Prograf (tacrolimus; n=12 studies,63 64 65 66 67 68 69 70 71 72 73 74 seven in kidney transplants, one in heart transplants, one in liver transplants, and three in a mixture of liver, kidney, or heart transplants), and Cellcept (mycophenolate mofetil; n=6 studies,75 76 77 78 79 80 five in kidney transplants and one in liver transplants). Neoral was compared with 12 different generics (Iminoral, Equoral, Gengraf, Cysporin, Zinograf-ME, Neoplanta, Consupren, SangCya (Sang-35), Sigmasporin Microral, Pliva, Cicloral, and Arpimune); Prograf was compared with four different generics (Tacni, Tacrobell, Adoport, and Sandoz-tacrolimus); and Cellcept was compared with five different generics (Myfenax, Medis, Linfonex, Mycept, and Myconol).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a study of cyclosporin, 8 another drug with narrow therapeutic window, confirmed bioequivalence between reference and generic drugs in the steady state, without significant intra-and interindividual variability, indicating that interchangeability between generic and reference drugs is possible. Aiming at reducing the impact of interindividual variability in bioequivalence tests for drugs with narrow therapeutic window, Health Canada limited the acceptable variability range between comparison variables in bioequivalence tests for these drugs.…”
Section: Interchangeability Between Drugs With the Same Active Princimentioning
confidence: 92%
“…However, transplant societies have raised concerns regarding the validity of extrapolating data derived from healthy subjects to the target patient populations [8][9][10] . Indeed, although most of the generic CsA conversion trials in stable renal transplant recipients found the tested products to have similar pharmacokinetic profiles compared to Neoral [11][12][13][14] , few others have reported significant differences between generic and innovator products [15,16] . Along the same line, in the de novo kidney transplant setting, some studies found similar renal graft outcomes with Neoral or generic CsA formulations [17,18] , whereas others indicated a higher rate of acute rejection with generic products [19,20] .…”
Section: Introductionmentioning
confidence: 99%